Differences in the spectrum of steroidogenic enzyme inhibition between Osilodrostat and Metyrapone in ACTH-dependent Cushing syndrome patients. Issue 2 (4th July 2022) - Bonnet-Serrano, Fidéline; Poirier, Jonathan; Vaczlavik, Anna; Laguillier-Morizot, Christelle; Blanchet, Benoît; Baron, Stéphanie; Guignat, Laurence; Bessiene, Laura; Bricaire, Léopoldine; Groussin, Lionel; Assié, Guillaume; Guibourdenche, Jean; et al.
Abstract: Introduction: Osilodrostat is a new 11β-hydroxylase inhibitor with a mode of action analogous to Metyrapone. The objective of this study was to compare steroidogenic profiles in patients treated with either Osilodrostat or Metyrapone for adrenocorticotrophic hormone (ACTH)-dependent Cushing's syndrome (CS). Methods: Patients followed up at Cochin hospital Endocrinology department between March 2019 and December 2021 for an ACTH-dependent CS, controlled by either Osilodrostat or Metyrapone, were included. A serum profile of five steroids (cortisol, 11-deoxycortisol, 17-hydroxyprogesterone, androstenedione and testosterone) was determined using UPLC- tandem mass spectrometry (UPLC-MS/MS). Results: Nineteen patients treated with Osilodrostat, eight patients treated with Metyrapone and six patients treated with consecutive Metyrapone then Osilodrostat were included. Hypocortisolism (basal cortisol <100 nmol/L) was found in 48% of patients treated with Osilodrostat and 7% of patients treated with Metyrapone. 11-deoxycortisol and androstenedione levels were higher in patients treated with Metyrapone (80.9 (2.2–688.4) and 14.9 (2.5–54.3) nmol/L, respectively) than in patients treated with Osilodrostat (10.3 (0.5–71.9) and 4.0 (0.3–13.3) nmol/L) ( P  = 0.0009 and P = 0.0005 ). Testosterone level in women was also higher in Metyrapone group (3.3 (0.93–4.82) nmol/L vs 1.31(0.13–5.09) nmol/L, P  = 0.0146 ). CYP11B1 activity (11-deoxycortisol/cortisol) was not significantly different between the two groups. CYP21A2 activity (17OHprogesterone/11-deoxycortisol) and CYP17A1 activity (17OHprogesterone/androstenedione) were significantly decreased in Osilodrostat group ( P  < 0.0001). Conclusion: In patients with ACTH-dependent CS, the use of CYP11B1 inhibitors in routine care suggests that Osilodrostat has a less specific effect on the inhibition of steroidogenic enzymes than Metyrapone. This might explain a smaller increase in 11-deoxycortisol and androgen levels in patients treated with Osilodrostat.